Imbalance of TGF-β1/BMP-7 pathways induced by M2-polarized macrophages promotes hepatocellular carcinoma aggressiveness - Ning, Junya (Mol Ther, 2021)
The transforming growth factor-beta (TGF-β) signaling pathway is the predominant cytokine signaling pathway in the development and progression of hepatocellular carcinoma (HCC). Bone morphogenetic protein (BMP), another member of the TGF-β superfamily, has been frequently found to participate in crosstalk with the TGF-β pathway. However, the complex interaction between the TGF-β and BMP pathways has not been fully elucidated in HCC. We found that the imbalance of TGF-β1/BMP-7 pathways was associated with aggressive pathological features and poor clinical outcomes in HCC. The induction of the imbalance of TGF-β1/BMP-7 pathways in HCC cells could significantly promote HCC cell invasion and stemness by increasing inhibitor of differentiation 1 (ID1) expression. We also found that the microRNA (miR)-17-92 cluster, originating from the extracellular vesicles (EVs) of M2-polarized tumor-associated macrophages (M2-TAMs), stimulated the imbalance of TGF-β1/BMP-7 pathways in HCC cells by inducing TGF-β type II receptor (TGFBR2) post-transcriptional silencing and inhibiting activin A receptor type 1 (ACVR1) post-translational ubiquitylation by targeting Smad ubiquitylation regulatory factor 1 (Smurf1). In vivo, short hairpin (sh)-MIR17HG and ACVR1 inhibitors profoundly attenuated HCC cell growth and metastasis by rectifying the imbalance of TGF-β1/BMP-7 pathways. Therefore, we proposed that the imbalance of TGF-β1/BMP-7 pathways is a feasible prognostic biomarker and recovering the imbalance of TGF-β1/BMP-7 pathways might be a potential therapeutic strategy for HCC.